Architectural Decoration of Christian Churches in Some Regions of Caucasus between 10th and 11thCenturies: An Attempt to Reconstruct the Decorative Syste - Ekaterina Yu. Endoltseva; Nikolay I. Bystritskiy (Anastasis: Research in Medieval Culture and Art)
In course of the long-term research on the architectural decoration of Christian churches in Abkhazia and Southern Ossetia, there has been gathered a great number of important materials (that help to correct the date of some groups of artefacts and to identify some new subjects, as well as to put them in the artistic context of the life of the Byzantine Empire and its periphery in the period between the 10th and the beginning of the 11th centuries). However, lapidary collections that originate from these regions have not been studied from the point of view of function and its reliefs. It is necessary to separate the fragments of the altar barriers from the ones of the facades of the Christian churches. Studying of the analogies from the neighboring regions (modern territory of Georgia, Armenia, Asia Minor, other parts of the Byzantine Empire) and using the modern methods of research (3D reconstructions) could permit to visualize many principal monuments (small forms and monumental decoration) that originate from the above-mentioned regions. Such research is important for the studying of the artistic culture of these regions in the period of the genesis of the self-conscience of their tribes (end of the 9th cent. – beginning of the 11th cent.) and their separation from the political and cultural influence of the hegemon, that is the Byzantine Empire. Reconstruction of some monuments (altar barriers, decorative system of the facades) and drafting of the typological lines could afford us to demonstrate the meaning of the two regions for the Christian culture of the Southern Caucasus in the period concerned. It is also important to show their interrelations with the neighboring territories. Actuality of the problem is proved by the active research led, for example, in Georgia, Russian Federation, France, etc. Originality of research is proved by the fact that small forms and facade decoration of the Christian churches in Abkhazia and Southern Ossetia in the period in question have not been systematically studied yet. The previous studies focused on the paleo Christian period and the dates supposed for some key monuments have been essentially corrected by recent research. Meanwhile, this territory (Western Georgia, passes between KarachayCherkessia, Kabardino-Balkaria, Abkhazia, Southern Ossetia and Racha) played a decisive role in the formation of the original type of medieval artistic Christian conscience.